2012
DOI: 10.1159/000337552
|View full text |Cite
|
Sign up to set email alerts
|

Food Intake, Diet Quality and Behavioral Problems in Children: Results from the GINI-plus/LISA-plus Studies

Abstract: Background/Aims: To assess the association between food intake and diet quality and behavioral problems at the 10-year follow-up of the two population-based birth cohorts of the studies German Infant Nutritional Intervention and ‘Influences of lifestyle-related factors on the immune system and the development of allergies in childhood’. Methods: Cross-sectional data on food intake over the past year were collected by a parent-reported food frequency questionnaire. Diet quality was based on reference values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
72
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 67 publications
(62 reference statements)
10
72
0
1
Order By: Relevance
“…Whilst it is important to consider the impact of socio-economic status (and indeed the developmental status of a country) on this relationship, given that both are established indicators of dietary patterns [38] and mental health outcomes [39], it remains relevant to consider and compare studies conducted in HICs. Several studies conducted in HICs have found associations between higher healthy dietary quality and lower depressive symptomology in adolescents [12, 14, 16, 17, 19], supporting the findings of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Whilst it is important to consider the impact of socio-economic status (and indeed the developmental status of a country) on this relationship, given that both are established indicators of dietary patterns [38] and mental health outcomes [39], it remains relevant to consider and compare studies conducted in HICs. Several studies conducted in HICs have found associations between higher healthy dietary quality and lower depressive symptomology in adolescents [12, 14, 16, 17, 19], supporting the findings of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Studies involving sugar and behavioral problems have been inconclusive, though correlation studies have been described as showing that among children, consumption of large amounts of sugar was associated with lowered attention spans (Bellisle, 2004;Soh et al, 2009) and controlled experimental studies have indicated that children who consumed greater amounts of sugar were not overly active (Bellisle, 2004;Soh et al, 2009). Although an earlier metaanalysis of nutrition in psychology studies indicated that sugar does not affect the behavior or cognitive abilities of children when consumed in high amounts (Wolraich et al, 1995), more recent cohort studies among young children found that low quality diets high in refined sugar resulted in increased levels of hyperactivity (Wiles et al, 2009) or likelihood of emotional symptoms (Kohlboeck et al, 2012). Higher intake of sugar-sweetened products and poor quality diet were found to be associated with a greater likelihood of behavioral problems in children (Kohlboeck et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Germany (0 to 17 years), [19][20][21][22][23] Finland (1 to 6 years), 24 Spain (2 to 24 years), [25][26][27] and Canada (older than 3 years). 28,29 A few dietary indices measured diet quality among children in Asian countries.…”
mentioning
confidence: 99%